Effects of Fluency Oriented Instruction on Motivation for Reading of Struggling Readers - Gene Mehigan (MDPI AG, 2020)
This paper looks at the effects of an intervention, based on fluency oriented reading instruction (FORI), on the motivation for reading among struggling readers in First Class in Irish primary schools. The intervention took place in learning support settings in three primary schools located in urban educationally disadvantaged communities in North Dublin. The study was conducted through a pragmatic lens with research questions framed to shed light on the motivation for reading of students in First Class from disadvantaged backgrounds. A mixed methods design with a concurrent triangulation strategy was employed, facilitating the exploration of multiple research questions using questionnaires and semi-structured interviews with teachers and parents and conversational interviews and surveys with students. The perspective of reading motivation guiding the study recognised the overlapping influences of teachers, parents and the student himself or herself. Findings, as reported by these research informants, indicate that the FORI intervention had a positive impact on the motivation for reading of struggling readers in First Class. In particular, the intervention was found to decrease students’ perceived difficulty with reading and increase their reading self-efficacy and orientation towards reading.